Prevention of high-fat/high-sugar diet-induced type 2 diabetes mellitus-associated non-alcoholic fatty liver disease in rats with fermented and raw Rosa roxburghii Tratt (Cili) juice - Zhang, Jingzhi; Li, Haizhi; Yang, Huiru; Zhu, Liying; Zhang, Yiqiong; Huang, Changyudong; Wang, Shuang; Duan, Yunfeng; Jiang, Zhaohui; Liu, Mi; Zhao, Shuyun; Pan, Wei (Frontiers in Nutrition, 2025)
IntroductionRosa roxburghii Tratt (Cili) is a medicinal and edible plant that has hypoglycemic, hypolipidemic, anti-inflammatory and antioxidant properties.MethodsTo compare and confirm the potential effects of spontaneous fermented/raw Cili juice (FCJ/RCJ) on type 2 diabetes mellitus (T2DM), the constituents of FCJ and RCJ were characterized and compared, high-fat/high-sugar diet (HFD) and streptozocin (STZ)-induced T2DM-associated non-alcoholic fatty liver disease (NAFLD) model rats were gavaged with FCJ/RCJ (1.5 mL/kg/day) for 20 weeks, after which serum, urine and liver and pancreas tissues were collected for experiments, and urine non-targeted metabolomics and liver transcriptomics analyses were conducted, and enhanced analysis of metabolomics results and the liver transcriptome.ResultsThe findings demonstrated that FCJ and RCJ ameliorated hyperglycemia, dyslipidemia, and abnormal hepatic function; mitigated hepatic lipid accumulation; and restored insulin expression levels. These two kinds of Cili juices can modulate disorders of glucose and lipid metabolism, have anti-inflammatory effects, and improve sterol metabolism and bile acid homeostasis. Joint analysis indicated that the antidiabetic effects of FCJ/RCJ in rats with T2DM-associated NAFLD are mediated through improvements in insulin sensitivity, fatty acid metabolism, and bile acid homeostasis. Notably, FCJ has a stronger anti-inflammatory effect, whereas RCJ preferentially regulates bile acid homeostasis and mitochondrial β-oxidation.ConclusionThe in vivo experiments of T2DM-associated NAFLD rats conducted in this study demonstrate that FCJ/RCJ has the potential to ameliorate metabolic disorders.